Factors Associated with Stillbirth Autopsy in Georgia and Utah, 2010–2014: The Importance of Delivery Location - Forsberg, Kaitlin; Christiansen-Lindquist, Lauren; Silver, Robert M. (American Journal of Perinatology, 2018)
Objective This article determines whether demographic, delivery, and medical factors are associated with stillbirth autopsy performance in Georgia and Utah.Study Design This study used fetal death certificates from 2010 to 2014 to determine which factors are associated with stillbirth autopsy performance in Georgia and Utah. Analyses were conducted using logistic regression with a predicted margins approach.Results The stillbirth autopsy rate was low in both states: 11.9% in Georgia (N = 5,610) and 23.9% in Utah (N = 1,425). In Utah, the autopsy rate significantly declined during the study period (p = 0.01). Stillbirths delivered outside of large metropolitan areas were less likely to receive an autopsy (medium/small metropolitans: prevalence ratioGA [PR] = 0.57, 95% confidence interval [CI]: 0.48–0.68 and PRUT = 0.48, CI: 0.38–0.59; nonmetropolitans: PRGA = 0.57, CI: 0.43–0.75 and PRUT = 0.37, CI: 0.21–0.63). In Georgia, autopsies were less common among stillbirths of Hispanic (vs. white) women (PR = 0.57, CI: 0.41–0.79), at earlier (vs. later) gestational ages (PR = 0.59, CI: 0.51–0.69), and of multiple birth pregnancies (PR = 0.71, CI: 0.53–0.96).Conclusion Despite strong evidence supporting the value of stillbirth autopsies, autopsy rates were low, especially outside metropolitan areas, where approximately half of stillbirths were delivered.
Keywords: stillbirth; autopsy; fetal death; fetal death certificate; perinatal pathology; vital records